Respuesta :
Step-by-step explanation:
2(x - 4) = 16
x - 4 = 16 / 2
x - 4 = 8
x = 8 + 4
x = 12
I think the answer would be x=12
2(x-4)=16
So the number in the parenthesis would need to end up equaling 8. This is because 2(8) = 16. So, using that, you would add 4 (the given number) and 8 (the number you need) to get 12. Then you check the equation.
2(12-4)=16
12-4=8
2(8) = 16
I hope this helps and I correct...
2(x-4)=16
So the number in the parenthesis would need to end up equaling 8. This is because 2(8) = 16. So, using that, you would add 4 (the given number) and 8 (the number you need) to get 12. Then you check the equation.
2(12-4)=16
12-4=8
2(8) = 16
I hope this helps and I correct...